Sports finance and management : real estate, media, and the new business of sport - Winfree, Jason (Jason A.) (New York : Taylor & Francis, 2019)
As the sport business continues to evolve, so too, does Sport Finance and Management. The first version of this book took an in-depth look at changes in the sport industry, including interconnecting financial issues between teams and their associated businesses, the nature of fan loyalty influences, and the impact of sponsorship on team revenues. This second edition updates each of these elements, introduces relevant case study examples in new chapters, and examines the impact of changes in facility design, media opportunities, and league and conference policies on the economic success of teams, the salaries earned by professional players, and the finances of collegiate athletics.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- United States -- Finance; Sports administration -- United States; Sports -- Economic aspects -- United States; GAMES / Gambling / Sports; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; TRAVEL / Special Interest / Sports; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Management Science